Diffuse Melanosis and Ascites due to Metastatic Malignant Melanoma - Sendagorta, Elena (ScientificWorldJournal, 2008)
We present a female patient who developed mucosal and skin hyperpigmentation due to metastatic malignant melanoma. Diffuse cutaneus melanosis is a rare entity that complicates a small percentage of metastatic melanomas, confering a fatal prognosis. We discuss briefly the current evidence on pathogenesis of melanosis arising from metastatic melanoma.